Control of Dynamic Voltage Restorer Using Novel Fast Two Vector Phase-Locked Loops Regulator - Almathnani, Ali; Lesewed , Ali; Alakshi , Jamal; Abuazoum , Saleh (Journal of Pure & Applied Sciences, 2021)
A fast two-vector Phase-locked loops (PLL) control has been proposed to control the phase and frequency of the grid voltage using 48-pulse switching. The novel controller senses the phase shift of the grid voltage as a frequency deviation by the load and locked to the positive sequence. The controller was designed to track the grid voltage angle and kept the grid frequency within the satisfying rang at all the time. The PI- controller was proposed to obtain the desired performance of the PLL. The fast PLL   phase shift of the grid voltage. The test results shows that the new design of controller can control the response of the positive sequence between -1.75p.u to 1.75p.u. With in-phase compensation. The proposed PLL controller has been simulated by using PSCAD/EMTD software package.